A comparative study on Ca content and distribution in two Gesneriaceae species reveals distinctive mechanisms to cope with high rhizospheric soluble calcium - Li, Wenlong; Xu, Falun; Chen, Shixuan; Zhang, Zhennan; Zhao, Yan; Jin, Yukuan; Li, Meijing; Zhu, Yan; Liu, Yongxiu; Yang, Yi; Deng, Xin (Frontiers in Plant Science, 2014)
Excessive Ca is toxic to plants thus significantly affects plant growth and species distribution in Ca-rich karst areas. To understand how plants survive high Ca soil, laboratory experiments were established to compare the physiological responses and internal Ca distribution in organ, tissue, cell and intracellular levels under different Ca levels for Lysionotus pauciflorus and Boea hygrometrica, two karst habitant Gesneriaceae species in Southwest China. In the controlled condition, L. pauciflorus could survive as high as 200 mM rhizospheric soluble Ca, attributed to a series of physiological responses and preferential storage that limited Ca accumulation in chloroplasts of palisade cells. In contrast, B. hygrometrica could survive only 20 mM rhizospheric soluble Ca, but accumulated a high level of internal Ca in both palisade and spongy cells without disturbance on photosynthetic activity. By phenotype screening of transgenic plants expressing high Ca-inducible genes from B. hygrometrica, the expression of BhDNAJC2 in A. thaliana was found to enhance plant growth and photosynthesis under high soluble Ca stress. BhDNAJC2 encodes a recently reported heat shock protein (HSP) 40 family DnaJ-domain protein. The Ca-resistant phenotype of BhDNAJC2 highlights the important role of chaperone-mediated protein quality control in Ca tolerance in B. hygrometrica. Taken together, our results revealed that distinctive mechanisms were employed in the two Gesneriaceae karst habitants to cope with a high Ca environment.